Digital Capability Alignment and Customer Value Creation: A Dynamic Capabilities Perspective on AI-Enabled Marketing and Supply Chain Analytics - Jedi, Mohammad A. L.; Ali, Ahmad; Shkeer, Amged Saleh; Al-Shaikh, Mustafa S. (International Review of Management and Marketing, 2026)
This research questions the concomitant impact of AI-based digital marketing and supply-chain analytics capabilities on customer experience with the digital supply-chain integration, and the digital maturity is used as a moderator variable of retail industry. Based on the DCT, AI-based marketing is envisaged as a sensing potential, supply-chain analytics as a seizing potential, and digital supply-chain integration as the reconfiguring mechanism that converts digital intelligence into the customer value. By using data gathered by using surveys with 487 respondents in the role of retail managers within Jordan and PLS-SEM analysis, the results suggest that supply-chain analytics abilities have a beneficial impact on digital integration and customer experience. Conversely, AI-based digital marketing has a statistically significant but negative effect on integration and customer experience, which suggests a lack of alignment between the front-end digital programs and the operational readiness on the back-end. Digital supply-chain integration moderates the correlation between the analytics and experience, whereas digital maturity strengthens the impacts of integration on customer experience. These findings highlight the paramount role played by the balanced capacity building and the cross functional alignment towards the sustainability of the value creation in the digital transformation of retail.